Combination 5-fluorouracil, folinic acid and cisplatin (LV5FU2-CDDP) followed by gemcitabine or the reverse sequence in metastatic pancreatic cancer: final results of a randomised strategic phase III trial (FFCD 0301). Issue 11 (14th October 2010) - Dahan, Laetitia; Bonnetain, Frank; Ychou, Marc; Mitry, Emmanuel; Gasmi, Mohamed; Raoul, Jean-Luc; Cattan, Stéphane; Phelip, Jean-Marc; Hammel, Pascal; Chauffert, Bruno; Michel, Pierre; Legoux, Jean-Louis; et al.
Abstract : Purpose: Gemcitabine is the standard chemotherapy for patients with metastatic pancreatic adenocarcinoma. Although the 5-fluorouracil (5FU), folinic acid and cisplatin combination (LV5FU2-CDDP) is an option, the optimal order of the regimens must be determined. The first strategic phase III trial comparing LV5FU2-CDDP followed by gemcitabine versus gemcitabine followed by LV5FU2-CDDP was conducted. Methods: Patients with metastatic pancreatic adenocarcinoma, performance status (PS) 0–2, without prior chemotherapy were randomly assigned (1:1) to receive either LV5FU2-CDDP followed by gemcitabine at disease progression or toxicity (Arm A), or the opposite sequence (Arm B). 202 patients had to be included and 170 deaths had to be observed to detect an expected improvement in median overall survival (OS) from 6.5 to 10 months in Arm A (two-sided α = 5% and β = 20%). Results: 202 patients were included (Arm A, 102; Arm B, 100). Median age, male/female ratio, PS 0–1 and previous surgery were similar in the two arms. After a median follow-up of 44 months, median OS in Arm A was 6.6 months versus 8.0 months in Arm B (p = 0.85). Median progression-free survival was similar between Arms A and B. More grade 3/4 toxicities were observed when LV5FU2-CDDP was administered as a first-line treatment compared with gemcitabine: 79% versus 64% (p = 0.018). Conclusion: This trial did not show any strategic advantage to using LV5FU2-CDDP as a first-line treatment and suggests that gemcitabine remains the standard first-line treatment. Sixty-one per cent of patients were able to receive a second line of chemotherapy.